Perkawinan Katolik sebagai Sakramen: Kajian Hukum Gereja dalam Konteks Pluralisme Agama di Barito Timur - Marianus Rago Kristeno; Yohanes Wilson B. Lena Meo (JURNAL PASTORAL KATEKETIK, 2025)
Marriage is one of the fundamental aspects of human life that not only involves social dimensions but also carries deep religious significance. The Catholic Church regards marriage as a Sacrament. In the pluralistic context of East Barito Regency, the understanding and appreciation of the sacramental value of Catholic marriage present a particular challenge. This study aims to analyze the meaning of Catholic marriage as a sacrament from the perspective of Church law and its application amid religious and cultural pluralism in East Barito Regency. The research employs a qualitative method with a library research approach, focusing on content analysis of primary sources such as the 1983 Code of Canon Law and magisterium Church documents, as well as secondary sources in theology, law, and pastoral studies. The data were analyzed descriptively and qualitatively through conceptual and normative approaches to examine the relationship between sacramental theology and canon law. The results show that Catholic marriage has two essential dimensions— theological and juridical— which unite in the sacred covenant between husband and wife. In the pluralistic context of East Barito, the Church faces challenges in applying canonical norms to traditional customs and mixed marriages, thus requiring a pastoral approach that is dialogical and inculturative. In conclusion, Church law serves not merely to regulate but to guide the faithful in living the sacrament of marriage as a sign of God’s love within a diverse society.